2017
DOI: 10.21873/anticanres.11881
|View full text |Cite
|
Sign up to set email alerts
|

Deepening a Simple Question: Can MSCs Be Used to Treat Cancer?

Abstract: In cancer, mesenchymal stem/stromal cells (MSCs) have been considered as vehicles for targeted delivery of drugs due to their inherent tropism toward primary and metastatic tumors. However, it is still unclear whether MSCs could be therapeutically explored without significant harm, since a great amound of evidence indicates that MSCs are able to exert both tumor-suppressive and pro-oncogenic effects. Here, we discuss how MSCs might adopt a pro- or anti-inflammatory profile in response to changes within the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 157 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…They include cancer vaccines, monoclonal antibodies, and cell-based therapies, such as chimeric antigen receptor (CAR) T-cell therapy [ 5 ]. Because of their enhanced tumor targeting and minimal off-target effects stem cell therapy is gaining ground and is becoming a popular choice for treatment against cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They include cancer vaccines, monoclonal antibodies, and cell-based therapies, such as chimeric antigen receptor (CAR) T-cell therapy [ 5 ]. Because of their enhanced tumor targeting and minimal off-target effects stem cell therapy is gaining ground and is becoming a popular choice for treatment against cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests a key role of MSCs in MET via the secretion of the hepatocyte growth factor, which has been associated with an aggressive phenotype and poor clinical prognosis in several types of solid tumors [17,18]. Last, since MSCs are being considered the most promising stem cell type for future regenerative medicine therapies [19], the revealed potential of altered MSCs to contribute to malignancies is of great concern and a limiting factor for otherwise efficient regenerative therapies [20,21]. The key question in this regard is therefore whether low-dose rate radiation exposures are capable of producing changes in the MSCs that can cause the transformation of stem cells into CSCs [22].…”
Section: Introductionmentioning
confidence: 99%
“…They are pluripotent stromal cells, which can differentiate into a variety of cell types, including osteoblasts, myocytes, and adipocytes, and are easy to obtain from many tissues [ 17 ]. MSCs are proposed to own therapeutic functions serving as agent carriers to deliver tumor targeting drug to OC cells [ 18 , 19 ]. Studies have reported that MSCs have the potential to treat various diseases, such as cancer [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%